A method for preparing high-purity bismuth based on fluorosilicic acid system and high-purity bismuth
By adopting specific treatment steps in the fluosilicate system, including energizing and removing impurities and adding bone glue and β-naphthol, the impurity content of the electrolyte is successfully reduced, and the problem of high-purity bismuth electrolyte in the prior art is solved, and the effective preparation of high-purity bismuth is achieved.
Patent Information
- Application Number
- CN202510008548.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when the fluorosilicate system prepares high purity bismuth, the electrolyte contains high miscellaneous content, making it difficult to meet the Pb and Cu standards of Bi99.999 in the YS/T 818-2012 standard.
By mixing fluosilicate and hydrogen peroxide, adding water to stabilize the capacity, adding excess bismuth powder while stirring, then turning on the impurity removal treatment, then adding fluosilicate to further remove impurity, finally adding bone glue and β-naphthol to prepare low-unity electrolyte, which is used to electrolyte to prepare high-purity bismuth.
The impurity content in the electrolyte was significantly reduced, and the obtained high-purity bismuth content was <0.7×10-4%, which met the requirements of Bi99.999 in the YS/T 818-2012 standard.
Smart Images

Figure CN119753760A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparing high-purity bismuth by electrolysis, and specifically relates to a method for preparing high-purity bismuth based on a fluorosilicic acid system and the high-purity bismuth. Background Art
[0002] At present, the preparation of high-purity bismuth with a purity of more than 99.999% mainly includes zone melting, vacuum distillation and electrolysis. The preparation of high-purity bismuth by zone melting is based on the segregation effect, which uses the difference in chemical potential of impurity elements in the solid and molten states of the main metal at the same temperature for directional migration and separation. It requires repeated melting-solidification to migrate impurities, which has the disadvantages of high energy consumption and low metal direct recovery rate, and is only suitable for small-scale production, which limits the development and application of this technology. The vacuum distillation method mainly uses the difference in saturated vapor pressure between metallic bismuth and impurities for impurity removal. The vacuum distillation process can effectively remove most of the high-boiling point impurities in bismuth, but the effect of removing impurities from low-boiling point impurity metals is poor, and it is difficult to achieve deep impurity removal in one distillation. It is only suitable for the removal of high-boiling point impurities in bismuth, and has the disadvantages of high energy consumption and low direct recovery rate, which limits the wide application of this technology. The electrolysis method has the advantages of high metal direct recovery rate and low energy consumption, but is limited by the electrolyte preparation technology. The prepared electrolyte contains high impurities and it is difficult to prepare qualified high-purity bismuth products.
[0003] At present, there are still studies on the preparation of high-purity bismuth by fluorosilicic acid system in the prior art. For example, in the open document "Experimental Study on the Production of 5N High-Purity Bismuth by Electrolysis of Refined Bismuth", fluorosilicic acid and industrial bismuth oxide were used to make liquid. Since the electrolyte obtained by making liquid contains high impurities, it is necessary to further obtain bismuth products by electrolysis using 99.99% refined bismuth as anode and copper plate as cathode. The obtained bismuth product contains 2.5×10 -4 %, Cu content is 2.9×10 -4 %, exceeding the Pb and Cu content standards of Bi99.999 in the YS / T 818-2012 standard. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing high-purity bismuth based on a fluorosilicic acid system.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0008] After the fluorosilicic acid and hydrogen peroxide are mixed, water is added to the mixture to make up the volume, and an excess of bismuth powder is added thereto while stirring. After the bismuth powder is added, stirring is continued. After the stirring is completed, filtering is performed to obtain a supernatant I and a filter residue;
[0009] The supernatant I is subjected to an electric impurity removal treatment to obtain an electric impurity removal solution;
[0010] Add fluorosilicic acid to the electric impurity removal solution while stirring it, continue stirring after the addition of fluorosilicic acid, and filter to obtain supernatant II and filter residue after the stirring is completed;
[0011] In this step, since chemically pure fluorosilicic acid contains 0.14% free fluoride ions and 0.16% free sulfate ions, when fluorosilicic acid is added, the impurities in the solution are purified due to the occurrence of precipitation reaction. The chemical reaction in this step is:
[0012] Zn 2+ +2F - =ZnF2↓
[0013] Ni 2+ +2F - =NiF2↓
[0014] Cu 2+ +2F - =CuF2↓
[0015] Fe 2+ +2F - =FeF2↓
[0016] Pb 2+ +SO4 2- =PbSO4↓
[0017] 2Bi 3+ +3SO4 2- =Bi2(SO4)3↓
[0018] 2Ag + +SO4 2- =Ag2SO4↓
[0019] Deionized water is first added to the supernatant II to make up the volume, and then bone glue and β-naphthol are added thereto, and stirred until the bone glue and naphthol are completely dissolved, thereby obtaining a low-impurity bismuth electrolyte;
[0020] By using low-impurity bismuth electrolyte as the solution carrier and passing electricity, high-purity bismuth products can be obtained.
[0021] As a preferred embodiment of the method for preparing high-purity bismuth based on a fluorosilicic acid system according to the present invention, the molar ratio of the bismuth powder to hydrogen peroxide is 2.2 to 2.4:3.
[0022] As a preferred embodiment of the method for preparing high-purity bismuth based on a fluorosilicic acid system according to the present invention, the addition rate of the bismuth powder is 1 to 100 g / min, and the stirring time after the addition of the bismuth powder is completed is 2 to 5 hours.
[0023] As a preferred embodiment of the method for preparing high-purity bismuth based on a fluorosilicic acid system according to the present invention, the concentration of fluorosilicic acid in the supernatant I is 60-80 g / L.
[0024] As a preferred embodiment of the method for preparing high-purity bismuth based on a fluorosilicic acid system according to the present invention, the conditions for the electric impurity removal treatment of the supernatant I include:
[0025] The above clear solution I is the electrolyte, bismuth is the anode, 316L stainless steel is the cathode, the bismuth anode is covered with a diaphragm bag, the cathode and the anode are evenly arranged, and the distance between the same electrodes is 6 to 10 cm, and the impurity removal current density is 30 to 60 A / m 2 The power-on time for impurity removal is 24 to 96 hours.
[0026] As a preferred embodiment of the method for preparing high-purity bismuth based on the fluorosilicic acid system of the present invention, the addition rate of fluorosilicic acid to the electric impurity removal solution is 0.05 to 0.2 L / min, and the stirring time after the addition of fluorosilicic acid is completed is 0.5 to 10 minutes.
[0027] As a preferred embodiment of the method for preparing high-purity bismuth based on a fluorosilicic acid system according to the present invention, the fluorosilicic acid concentration in the supernatant II is 120-150 g / L, and the bismuth ion concentration is 80-100 g / L.
[0028] As a preferred embodiment of the method for preparing high-purity bismuth based on the fluorosilicic acid system of the present invention, the concentration of bone glue in the low-impurity bismuth electrolyte is 0.1-0.5 g / L, and the concentration of β-naphthol is 0.1-0.5 mg / L.
[0029] As a preferred embodiment of the method for preparing high-purity bismuth based on a fluorosilicic acid system according to the present invention, the conditions for electrifying the low-doped bismuth electrolyte as a solution carrier include:
[0030] The electrolyte is low-doped bismuth electrolyte, bismuth is used as anode, 316L stainless steel is used as cathode, bismuth anode is covered with diaphragm bag, cathode and anode are evenly arranged, and the distance between the same poles is 6-10cm, and the current density is 30-60A / m 2 The cathode out of the slot time is 24 to 96 hours.
[0031] It should be noted that in this step, the cathode bismuth gradually grows, and the obtained cathode bismuth gradually becomes thicker, and the cathode needs to be removed from the tank and replaced.
[0032] Another object of the present invention is to provide a high-purity bismuth, wherein the impurity content of the high-purity bismuth is less than 0.7×10 -4 %.
[0033] Beneficial effects of the present invention:
[0034] The present invention aims at the problem of high impurity content in the new electrolyte solution in the electrolysis preparation of high-purity bismuth by fluosilicic acid system. Chemically pure fluosilicic acid, water with an electrical conductivity of less than 10 μS / cm, hydrogen peroxide meeting the 27.5% superior product standard of GB / T 1616-2014, and bismuth powder with impurities meeting the Bi99.99 standard in GB / T 915-2010 and a mesh number of 80 to 325 are used as raw materials, and the impurities are controlled from the source to prepare a solution with a fluosilicic acid concentration of 60 to 80 g / L and a bismuth ion concentration of 140 to 160 g / L. Then, the obtained liquid-making solution is electrified under certain conditions to remove impurities, and an electrified impurity-removed solution is obtained. Fluosilicic acid is added to the electrified impurity-removed solution for further impurity removal, so that the impurity content of the solution is further reduced. Finally, gelatin and β-naphthol solution are added to prepare a low-impurity electrolyte with low impurity content. The low-impurity electrolyte prepared by the technical invention can be used for electrolytic preparation of high-purity bismuth above 5N. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0036] Figure 1 The present invention is a process flow chart for preparing high-purity bismuth. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] The raw materials used in the present invention are all commercially available in the art, specifically:
[0041] Chemically pure fluorosilicic acid, water with a conductivity of less than 10μS / cm, hydrogen peroxide that meets the 27.5% superior product standard of GB / T 1616-2014, bismuth powder with impurities that meets the Bi99.99 standard in GB / T 915-2010 and a mesh number of 80 to 325 meshes, and bismuth anode that meets the Bi99.99 grade in GB / T 915-2010 are used.
[0042] Example 1
[0043] Reference Figure 1 This embodiment provides a method for preparing high-purity bismuth based on a fluorosilicic acid system, specifically:
[0044] 1) 11.444 L of fluorosilicic acid and 3.052 L of hydrogen peroxide were mixed and water was added to make the volume 25 L. 4500 g of 200 mesh bismuth powder was added thereto at a rate of 5 g / min while stirring at 350 rpm. After the bismuth powder was added, stirring was continued for 5 h. After stirring, supernatant I and filter residue were obtained by filtration. Fluorosilicic acid (g / L), Bi (g / L) and bismuth (g / L) in supernatant I were measured. 3+ The concentrations of impurities (mg / L) and their contents are shown in Table 1.
[0045] Table 1 Fluorosilicic acid (g / L), Bi in supernatant I 3+ (g / L) and impurity concentration (mg / L)
[0046]
[0047] 2) The above supernatant I is used as electrolyte, bismuth is used as anode, 316L stainless steel is used as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 40A / m 2 The impurities were removed by electricity for 72 hours under the above conditions to obtain an impurity-removing solution.
[0048] 2) While stirring the electric impurity removal solution at 350 rpm, 9.799 L of silicic acid was added to the stirred solution at a rate of 0.1 L / min. After the addition was completed, stirring was continued for 3 minutes. After the stirring was completed, supernatant II and filter residue were obtained by filtration.
[0049] 3) Add water to the supernatant II to make it 46.725L, add 23.4g of bone glue and 23.4mg of naphthol, stir the solution at a stirring speed of 400rpm until the bone glue and naphthol are completely dissolved, and obtain a low-impurity bismuth electrolyte, wherein fluorosilicic acid (g / L), Bi 3+ The concentrations of impurities (mg / L) and the concentrations of iodine (g / L) are shown in Table 2.
[0050] Table 2 Fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentration (mg / L)
[0051]
[0052] 5) Using 30L low-impurity electrolyte as electrolyte, bismuth as anode, 316L stainless steel as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 60A / m 2 Under the above conditions, the power was turned on for 48 hours to obtain a high-purity bismuth product, the impurity content of which is shown in Table 3.
[0053] Table 3 Bismuth product impurities (10 -4 % )
[0054]
[0055] Example 2
[0056] 1) 10.678 L of fluorosilicic acid and 2.952 L of hydrogen peroxide were mixed and the volume was fixed to 25 L with water. 4010 g of 120 mesh bismuth powder was added thereto at a rate of 3 g / min while stirring at 4000 rpm. After the bismuth powder was added, stirring was continued for 4.5 h. After stirring, supernatant I and filter residue were obtained by filtration. Fluorosilicic acid (g / L), Bi (g / L) and bismuth (g / L) in supernatant I were measured. 3+ The concentrations of impurities (mg / L) and the concentrations of iodine (g / L) are shown in Table 4.
[0057] Table 4 Fluorosilicic acid (g / L), Bi in supernatant I 3+ (g / L) and impurity concentration (mg / L)
[0058]
[0059] 2) The above supernatant I is used as electrolyte, bismuth is used as anode, 316L stainless steel is used as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 60A / m 2 The impurities were removed by electricity for 48 hours under the above conditions to obtain an impurity-removing solution.
[0060] 3) While stirring the electric impurity removal solution at 350 rpm, 7.662 L of silicic acid was added to the stirred solution at a rate of 0.15 L / min. After the addition was completed, stirring was continued for 5 minutes. After the stirring was completed, supernatant II and filter residue were obtained by filtration.
[0061] 4) Add deionized water to the supernatant II to make the volume to 42.647 L, then add 15.5 g of bone glue and 15.5 mg of naphthol, and stir the solution at a stirring speed of 350 rpm until the bone glue and naphthol are completely dissolved, thus obtaining a low-impurity bismuth electrolyte, wherein fluorosilicic acid (g / L), Bi 3+ The concentrations of impurities (g / L) and impurities (mg / L) are shown in Table 5.
[0062] Table 5 Fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentration (mg / L)
[0063]
[0064] 5) Using 30L low-impurity electrolyte as electrolyte, bismuth as anode, 316L stainless steel as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 60A / m 2 Under the above conditions, the power was turned on for 48 hours to obtain a high-purity bismuth product, the impurity content of which is shown in Table 6.
[0065] Table 6 Bismuth product impurities (10 -4 % )
[0066]
[0067] Example 3
[0068] 1) 11.452 L of fluorosilicic acid and 3.156 L of hydrogen peroxide were mixed and the volume was fixed to 25 L with water. 4456 g of 100 mesh bismuth powder was added thereto at a rate of 2 g / min while stirring at 300 rpm. After the addition of bismuth powder, stirring was continued for 4.8 h. After stirring was completed, supernatant I and filter residue were obtained by filtration. Fluorosilicic acid (g / L), Bi (g / L) and bismuth (g / L) of supernatant I were obtained. 3+ The concentrations of impurities (g / L) and impurities (mg / L) are shown in Table 7.
[0069] Table 7 Fluorosilicic acid (g / L), Bi in supernatant I 3+ (g / L) and impurity concentration (mg / L)
[0070]
[0071] 2) The above supernatant I is used as electrolyte, bismuth is used as anode, 316L stainless steel is used as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the same pole spacing is 10cm in uniform arrangement, and the current density is 50A / m 2 The impurities were removed by electricity under the above conditions for 70 hours to obtain an impurity-removing solution.
[0072] 3) While stirring the electric impurity removal solution at 380 rpm, 8.088 L of silicic acid was added to the stirred solution at a rate of 0.08 L / min. After the addition was completed, stirring was continued for 8 minutes. After the stirring was completed, supernatant II and filter residue were obtained by filtration.
[0073] 4) Add deionized water to the supernatant II to make the volume to 43.056 L, then add 8.6 g of bone glue and 8.6 mg of naphthol, and stir the solution at a stirring speed of 380 rpm until the bone glue and naphthol are completely dissolved, thus obtaining a low-impurity bismuth electrolyte, wherein fluorosilicic acid (g / L), Bi 3+ The concentrations of impurities (g / L) and impurities (mg / L) are shown in Table 8.
[0074] Table 8 Fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentration (mg / L)
[0075]
[0076] 5) Using 30L low-impurity electrolyte as electrolyte, bismuth as anode, 316L stainless steel as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 60A / m 2 Under the above conditions, the power was turned on for 48 hours to obtain a high-purity bismuth product, the impurity content of which is shown in Table 9.
[0077] Table 9 Bismuth product impurities (10 -4 % )
[0078]
[0079] Comparative Example 1
[0080] This comparative example cites the published document "Experimental Study on the Production of 5N High-Purity Bismuth by Electrolysis of Refined Bismuth". The electrolyte prepared by this scheme contains impurities as shown in Table 10, and the impurities of the obtained bismuth product are shown in Table 11.
[0081] Table 11 Impurities in electrolyte (mg / L)
[0082]
[0083] Table 12 Bismuth product impurities (10 -4 % )
[0084]
[0085] The results of Tables 1 to 12 show that the electrolytes obtained by the preparation methods of Examples 1 to 3 of the present invention contain significantly lower impurities of Cu, Pb, Ag, Cu, As, Zn, and Fe than those prepared in the public document "Experimental Study on the Production of 5N High-Purity Bismuth by Electrolysis of Refined Bismuth", and the impurities in the obtained high-purity bismuth are significantly lower. The impurities in the bismuth product obtained by electrolysis meet the requirements of Bi99.999 high-purity bismuth in the YS / T 818-2012 standard, and the total amount of impurities does not exceed 0.652×10 -4 %.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is that the electric impurity removal treatment of the supernatant I is omitted:
[0088] 1) 11.444 L of fluorosilicic acid and 3.052 L of hydrogen peroxide were mixed and the volume was fixed to 25 L with water. 4500 g of 200 mesh bismuth powder was added thereto at a rate of 5 g / min while stirring at 350 rpm. After the bismuth powder was added, stirring was continued for 5 h. After stirring, supernatant I and filter residue were obtained by filtration. Fluorosilicic acid (g / L), Bi (g / L) and bismuth (g / L) of supernatant I were obtained. 3+ (g / L) and impurity concentrations (mg / L) are shown in Table 13.
[0089] Table 13 Fluorosilicic acid (g / L), Bi in supernatant I 3+ (g / L) and impurity concentration (mg / L)
[0090]
[0091] 2) While stirring the electric impurity removal solution at 350 rpm, 9.799 L of silicic acid was added to the stirred solution at a rate of 0.1 L / min. After the addition was completed, stirring was continued for 3 minutes. After the stirring was completed, supernatant II and filter residue were obtained by filtration.
[0092] 3) Add water to the supernatant II to make it 46.725 L, add 23.4 g of bone glue and 23.4 mg of naphthol, and stir the solution at a stirring speed of 400 rpm until the bone glue and naphthol are completely dissolved, thereby obtaining a bismuth electrolyte, wherein fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentrations (mg / L) are shown in Table 14.
[0093] Table 14 Fluorosilicic acid (g / L), Bi in bismuth electrolyte 3+ (g / L) and impurity concentration (mg / L)
[0094]
[0095] 4) Using 30L bismuth electrolyte as carrier, bismuth as anode, 316L stainless steel as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 60A / m 2 Under the above conditions, the power was turned on for 48 hours to obtain a high-purity bismuth product, the impurity content of which is shown in Table 15.
[0096] Table 15 Bismuth product impurities (10 -4 % )
[0097]
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that step 3) of acid purification of the solution after the electric impurity removal is omitted:
[0100] 1) Fluorosilicic acid 13.524, hydrogen peroxide 1.936L, bismuth powder 2688g and water were used as raw materials for oxidation to obtain 30L of supernatant containing 149.57g / L of fluorosilicic acid and 79.44g / L of bismuth. The supernatant contained 149.57g / L of fluorosilicic acid and 79.44g / L of bismuth. 3+ (g / L) and impurity concentrations (mg / L) are shown in Table 16;
[0101] Table 16 Fluorosilicic acid (g / L), Bi in supernatant 3+ (g / L) and impurity concentration (mg / L)
[0102]
[0103] 2) The above clear liquid is used as electrolyte, bismuth is used as anode, 316L stainless steel is used as cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 40A / m 2 The impurities were removed by electricity for 72 hours under the above conditions to obtain an impurity-removing solution.
[0104] 3) 15g of bone glue and 15mg of naphthol were added to the electrified impurity removal solution, and the solution was stirred at a stirring speed of 400rpm until the bone glue and naphthol were completely dissolved, thereby obtaining a bismuth electrolyte solution, wherein fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentrations (mg / L) are shown in Table 17.
[0105] Table 17 Fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentration (mg / L)
[0106]
[0107] 4) Using 30L bismuth electrolyte as the solution carrier, bismuth as the anode, 316L stainless steel as the cathode, the bismuth anode is covered with a polyester fiber diaphragm bag, and the spacing between the electrodes is evenly arranged with a current density of 60A / m 2 Under the above conditions, the power was turned on for 48 hours to obtain a high-purity bismuth product, the impurity content of which is shown in Table 18.
[0108] Table 18 Bismuth product impurities (10 -4 % )
[0109]
[0110] Comparative Example 4
[0111] This comparative example is different from Example 1 in that step 2) and step 3) of the electric impurity removal treatment and acid impurity removal process of the supernatant I are omitted:
[0112] 1) Add water to 13.524 g of fluorosilicic acid and 1.936 L of hydrogen peroxide to make up to volume, add 2688 g of 200 mesh bismuth powder at a rate of 5 g / min, continue stirring for 5 h after the addition of bismuth powder, and filter to obtain 30 L of supernatant containing 149.57 g / L of fluorosilicic acid and 79.44 g / L of bismuth;
[0113] 2) Add 15 g of bone glue and 15 mg of β-naphthol to the supernatant, and stir at a stirring speed of 380 rpm until the bone glue and naphthol are completely dissolved to obtain a bismuth electrolyte, wherein fluorosilicic acid (g / L), Bi 3+ (g / L) and impurity concentrations (mg / L) are shown in Table 19.
[0114] Table 19 Fluorosilicic acid (g / L), Bi in bismuth electrolyte 3+ (g / L) and impurity concentration (mg / L)
[0115]
[0116] 3) Using bismuth electrolyte as carrier, bismuth as anode, 316L stainless steel as cathode, and polyester fiber diaphragm bag as bismuth anode, the spacing between the electrodes is 8cm and the current density is 60A / m 2 The bismuth product was obtained by applying power for 48 hours under the above conditions, and the impurity content was shown in Table 20.
[0117] Table 20 Bismuth product impurities (10 -4 % )
[0118]
[0119] It can be seen from the results of Comparative Examples 2 to 3 that by omitting any step in the present invention, a high-purity bismuth product equivalent to that in Example 1 cannot be obtained.
[0120] In summary, the present invention aims at the problem of high impurity content in the new electrolyte solution in the electrolysis of high-purity bismuth in the fluorosilicic acid system. Chemically pure fluorosilicic acid, water with a conductivity of less than 10 μS / cm, hydrogen peroxide that meets the 27.5% superior product standard of GB / T 1616-2014, and bismuth powder containing impurities that meets the Bi99.99 standard in GB / T 915-2010 and has a mesh number of 80 to 325 meshes are used as raw materials. The impurities are controlled from the source to prepare a solution with a fluorosilicic acid concentration of 60 to 80 g / L and a bismuth ion concentration of 140 to 160 g / L. Then, the obtained liquid-making solution is electrified under certain conditions to remove impurities, and an electrified impurity-removed solution is obtained. Then, the electrified impurity-removed solution is further impurity-removed by adding fluorosilicic acid to the electrified impurity-removed solution, so that the impurity content of the solution is further reduced. Finally, gelatin and β-naphthol solution are added to prepare a low-impurity electrolyte with a low impurity content. The low-impurity electrolyte prepared by the present technical invention can be used for electrolytic preparation of high-purity bismuth above 5N.
[0121] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing high-purity bismuth based on a fluorosilicic acid system, characterized in that: include, After the fluorosilicic acid and hydrogen peroxide are mixed, water is added to the mixture to make up the volume, and an excess of bismuth powder is added thereto while stirring. After the bismuth powder is added, stirring is continued. After the stirring is completed, filtering is performed to obtain a supernatant I and a filter residue; The supernatant I is subjected to an electric impurity removal treatment to obtain an electric impurity removal solution; Add fluorosilicic acid to the electric impurity removal solution while stirring it, continue stirring after the addition of fluorosilicic acid, and filter to obtain supernatant II and filter residue after the stirring is completed; Deionized water is first added to the supernatant II to make up the volume, and then bone glue and β-naphthol are added thereto, and stirred until the bone glue and naphthol are completely dissolved, thereby obtaining a low-impurity bismuth electrolyte; By using low-impurity bismuth electrolyte as the solution carrier and passing electricity, high-purity bismuth products can be obtained.
2. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 1, characterized in that: The molar ratio of the bismuth powder to hydrogen peroxide is 2.2-2.4:
3.
3. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 2, characterized in that: The bismuth powder is added at a speed of 1 to 100 g / min, and the stirring time after the bismuth powder is added is 2 to 5 hours.
4. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 1, characterized in that: The concentration of fluorosilicic acid in the supernatant I is 60-80 g / L.
5. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 4, characterized in that: The conditions for the electric impurity removal treatment of the supernatant I include: The above clear solution I is the electrolyte, bismuth is the anode, 316L stainless steel is the cathode, the bismuth anode is covered with a diaphragm bag, the cathode and the anode are evenly arranged, and the distance between the same electrodes is 6 to 10 cm, and the impurity removal current density is 30 to 60 A / m 2 The power-on time for impurity removal is 24 to 96 hours.
6. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 1, characterized in that: The rate of adding fluorosilicic acid into the electric impurity removal solution is 0.05 to 0.2 L / min, and the stirring time after the addition of fluorosilicic acid is completed is 0.5 to 10 minutes.
7. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 1, characterized in that: The concentration of fluorosilicic acid in the supernatant II is 120-150 g / L, and the concentration of bismuth ions is 80-100 g / L.
8. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 1, characterized in that: The concentration of bone glue in the low-impurity bismuth electrolyte is 0.1-0.5 g / L, and the concentration of β-naphthol is 0.1-0.5 mg / L.
9. The method for preparing high-purity bismuth based on a fluorosilicic acid system according to claim 8, characterized in that: The conditions for electrifying with low-doped bismuth electrolyte as the solution carrier include: The electrolyte is low-doped bismuth electrolyte, bismuth is used as anode, 316L stainless steel is used as cathode, bismuth anode is covered with diaphragm bag, cathode and anode are evenly arranged, and the distance between the same poles is 6-10cm, and the current density is 30-60A / m 2 The cathode out of the slot time is 24 to 96 hours.
10. The high-purity bismuth prepared by the method according to any one of claims 1 to 9, characterized in that: The impurity content of the high-purity bismuth is less than 0.7×10 -4 %.
Citation Information
Cited By
Method for preparing high-purity bismuth by removing impurity lead in refined bismuth through oxidation slagging
CN121538466A
Method for preparing high-purity bismuth through electrolytic refining and electrolysis system
CN121853072A